PROPERTIES OF ASPHALT CONCRETE WITH A FIBROUS POLYMER ADDITIVES - , В. К., О. О., Д. Ю., К. В., О. О. (Municipal economy of cities. Series: «Economy science», 2013)
The results of experimental studies of the physical and mechanical properties of asphalt concrete types with different particle size fibrous polymeric additive.